Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1111/j.1600-9657.1997.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of apex locator

Abstract: An evaluation of the accuracy of the "Root ZX" apex locator was conducted on 20 single-rooted teeth that had been extracted because of severe disease or orthodontic treatment. After the pulp chamber had been accessed and the tooth length determined using the Root ZX apparatus, the file was fixed to the tooth with light-cured composite resin. After extraction, the tooth was longitudinally ground with a diamond bur until the file was visible. The distance between the file tip and the apical foramen was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 13 publications
8
32
1
Order By: Relevance
“…By exposing the apical part of 20 permanent teeth, Wrbas et al (8) reported that the file tip was identified 0.12 and 0.15 mm short of the major foramen when using the Root ZX and Raypex 5, respectively. Vajrabhaya et al (23) found that the file tips were determined on average to be 0.2 mm coronal to the apical foramen when using the Root ZX on permanent teeth. However, in an ex vivo study of Pascon et al (12) on sixty extracted teeth, the file tip was found 0.69 mm and 1.10 mm coronal to the major foramen for the Raypex 5 and Elements Apex Locator, respectively, which were greater than the results in this study (0.376 mm for the Raypex 5 and 0.383 mm for the Elements Apex Locator).…”
Section: Discussionmentioning
confidence: 99%
“…By exposing the apical part of 20 permanent teeth, Wrbas et al (8) reported that the file tip was identified 0.12 and 0.15 mm short of the major foramen when using the Root ZX and Raypex 5, respectively. Vajrabhaya et al (23) found that the file tips were determined on average to be 0.2 mm coronal to the apical foramen when using the Root ZX on permanent teeth. However, in an ex vivo study of Pascon et al (12) on sixty extracted teeth, the file tip was found 0.69 mm and 1.10 mm coronal to the major foramen for the Raypex 5 and Elements Apex Locator, respectively, which were greater than the results in this study (0.376 mm for the Raypex 5 and 0.383 mm for the Elements Apex Locator).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the superimposition of bony structures hinders the identification of the radiographic apex of some teeth. Moreover, the interpretation of radiographs is subjective and involves quality issues like distortion and magnification (Vajrabhaya and Tepmongkol, 1997;Weiger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Vajrabheye et al 13 showed that accuracy of Root ZX with an accuracy rate of 100% when an error of ± 0.5 mm clinically. Falcheta and Castellucci 14 assessed the accuracy of Root ZX with a precise measurement in 91% cases (n = 100).…”
Section: Methodsmentioning
confidence: 99%